How do you differentiate #f(x)=sqrt(cose^(4x)# using the chain rule.?

1 Answer

Answer:

#f' (x)=(-2*e^(4x)*sin e^(4x))/(sqrt(cos e^(4x)))#

Explanation:

We start from the given
#f(x)=sqrt(cos e^(4x))#

#f' (x)=1/(2sqrt(cos e^(4x)))*d/dx(cos e^(4x))#

#f' (x)=1/(2sqrt(cos e^(4x)))*(-sin e^(4x))*d/dx(e^(4x))#

#f' (x)=1/(2sqrt(cos e^(4x)))*(-sin e^(4x))(e^(4x))d/dx(4x)#

#f' (x)=1/(2sqrt(cos e^(4x)))*(-sin e^(4x))(e^(4x))*4#

#f' (x)=(-2*e^(4x)*sin e^(4x))/(sqrt(cos e^(4x)))#

God bless....I hope the explanation is useful.